Electric Probe Measurements of the Poloidal Velocity in the Scrape‐Off Layer of ASDEX Upgrade. Issue 3 (April 2014) - Mehlmann, F.; Costea, S.; Schrittwieser, R.; Naulin, V.; Rasmussen, J. J.; Müller, H. W.; Nielsen, A. H.; Vianello, N.; Carralero, D.; Rohde, V.; Lux, C.; Ionita, C.; et al.
Abstract A reciprocating probe head with six pins was used for localized measurements of electric fields and densities in the scrape‐off layer (SOL) of ASDEX Upgrade (AUG) up to the edge shear layer (SL) near the Last Closed Flux Surface (LCFS). The edge SL is characterized by a strong sudden change in the poloidal velocity vθ close to the separatrix. The probes were used to determine this velocity by different methods which are critically compared to each other concerning their reliability. By the first method the poloidal velocity was deduced from the radial electric field Er measured by two radially staggered probe pins, with vθ being due to the Er × Bϕ‐drift (Bϕ is the toroidal field). The two other methods utilized the cross correlation of two poloidally staggered ion‐biased probes and two poloidally staggered floating probes, respectively. In this case the time lags with maximum cross correlation were used to determine the poloidal velocity and its jump, yielding comparable results to the first method. Also the method of conditional averaging was applied to the latter signals. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)